Global, regional, and national trends in haemoglobin concentration and prevalence of total and severe anaemia in children and pregnant and non-pregnant women for 1995-2011: a systematic analysis of population-representative data - Gretchen A Stevens, DSc; Mariel M Finucane, PhD; Luz Maria De-Regil, DrSc; Christopher J Paciorek, PhD; Seth R Flaxman, BA; Francesco Branca, PhD; Juan Pablo Peña-Rosas, MD; Prof. Zulfiqar A Bhutta, PhD; Prof. Majid Ezzati, PhD (Elsevier, 2013)
Background: Low haemoglobin concentrations and anaemia are important risk factors for the health and development of women and children. We estimated trends in the distributions of haemoglobin concentration and in the prevalence of anaemia and severe anaemia in young children and pregnant and non-pregnant women between 1995 and 2011. Methods: We obtained data about haemoglobin and anaemia for children aged 6-59 months and women of childbearing age (15-49 years) from 257 population-representative data sources from 107 countries worldwide. We used health, nutrition, and household surveys; summary statistics from WHO's Vitamin and Mineral Nutrition Information System; and summary statistics reported by other national and international agencies. We used a Bayesian hierarchical mixture model to estimate haemoglobin distributions and systematically addressed missing data, non-linear time trends, and representativeness of data sources. We quantified the uncertainty of our estimates. Findings: Global mean haemoglobin improved slightly between 1995 and 2011, from 125 g/L (95% credibility interval 123-126) to 126 g/L (124-128) in non-pregnant women, from 112 g/L (111-113) to 114 g/L (112-116) in pregnant women, and from 109 g/L (107-111) to 111 g/L (110-113) in children. Anaemia prevalence decreased from 33% (29-37) to 29% (24-35) in non-pregnant women, from 43% (39-47) to 38% (34-43) in pregnant women, and from 47% (43-51) to 43% (38-47) in children. These prevalences translated to 496 million (409-595 million) non-pregnant women, 32 million (28-36 million) pregnant women, and 273 million (242-304 million) children with anaemia in 2011. In 2011, concentrations of mean haemoglobin were lowest and anaemia prevalence was highest in south Asia and central and west Africa. Interpretation: Children's and women's haemoglobin statuses improved in some regions where concentrations had been low in the 1990s, leading to a modest global increase in mean haemoglobin and a reduction in anaemia prevalence. Further improvements are needed in some regions, particularly south Asia and central and west Africa, to improve the health of women and children and achieve global targets for reducing anaemia. Funding: Bill & Melinda Gates Foundation, Grand Challenges Canada, and the UK Medical Research Council.